In Pursuit of an Orientation for Life-preparation: A Case Study of the Subject Mathematical Literacy in South Africa. Issue 3 (2nd September 2017) - North, Marc
Abstract : Current practices in the South African secondary school subject Mathematical Literacy afford a limiting education experience for thousands of learners, the majority of whom are black and located in poor socio-economic environments: learners are confronted with pseudo-realistic contexts and engage only elementary mathematical contents. The consequence is limited mathematical competence and preparation for real-world participation, and dilution of their aspirations and hopes. This article employs a case study method to highlight the problematic nature of current practices and offers theoretically and analytically informed generalisations of an alternative structure of practice centred on the notion of a life-preparedness orientation. Theoretically, Bernstein's work on horizontal and vertical discourses is used to identify the discursive structure of the practices associated with this orientation and to distinguish these from mathematical practice. Analytically, the orientation is characterised by a dominant agenda for sense-making in authentic contextual scenarios, and is facilitated through engagement with four domains of practice comprising everyday knowledge, mathematical competency, modelling and criticality borne of contextual reasoning and reflective knowing. Each of these characteristics is demonstrated in reference to a text-based task drawn from the subject Mathematical Literacy. The requirement for further research to assess the realisability of this construct in assessment and pedagogic practices, and the associated complexities of this, is highlighted.